2020
DOI: 10.20398/jscr.v11i2.21090
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Renal Transplant Surgery in Adults

Abstract: Renal transplant surgery may be associated with important perioperative complications. In this scenario, the anesthetic technique should provide optimal conditions for the surgical team, guarantee hemodynamic stability and kidney perfusion, and adequate analgesia. Preoperative evaluation should always be performed. In the intraoperative period, standard monitoring is sufficient in most cases. General balanced anesthesia, alone or in combination with spinal anesthesia or peripheral block, is the technique of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…About half the mortality of patients on dialysis is due to heart failure and cardiovascular disease is the leading cause of death (and therefore graft loss) after renal transplantation 13 . Similarly pulmonary function test (PFT's) were done in cases where indicated especially with type 1 diabetes 14 . We have found that few of our patients were taking multiple anti-hypertensive drugs when they landed in OR (operating room) with poor control of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…About half the mortality of patients on dialysis is due to heart failure and cardiovascular disease is the leading cause of death (and therefore graft loss) after renal transplantation 13 . Similarly pulmonary function test (PFT's) were done in cases where indicated especially with type 1 diabetes 14 . We have found that few of our patients were taking multiple anti-hypertensive drugs when they landed in OR (operating room) with poor control of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia was performed according to the institutional protocol [ 8 ]. Standard monitoring with electrocardiography, noninvasive blood pressure measurement, pulse oximetry, nasopharyngeal thermometry, and capnography was done for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Balanced crystalloids, such as lactated Ringer’s (LR) and PlasmaLyte (PL), are closer to plasma in composition and have increasingly been used as alternatives to NS in various scenarios. Although these fluids contain physiological concentrations of potassium, they are believed to prevent hyperkalemia owing to their alkalizing properties [ 7 , 8 ]. In light of the ongoing debate as to which crystalloid is the most appropriate in patients undergoing kidney transplants, we conducted a randomized controlled trial to compare the effects of intraoperative NS, LR, and PL on acid-base status and electrolyte concentration.…”
Section: Introductionmentioning
confidence: 99%